AN ANALYSIS OF THE EFFECT OF YOGYAKARTA’S PRIVILEGE FUND ON POVERTY REDUCTION - Nuryana Nurul Hasanah; Jaka Sriyana; Saryana Saryana (Jurnal Ilmu Ekonomi dan Pembangunan, 2025)
In September 2015, the United Nations (UN) set Sustainable Development Goals (SDGs) to improve global prosperity, with the first SDG focusing on the elimination of poverty. In Indonesia, the poverty rate in 2023 is 9.36%, while in Yogyakarta it is higher at 11.04%. As a special region, Yogyakarta receives a Privileged Fund that continues to increase every year, with one of its performance indicators being poverty reduction. This study analyzes the impact of the Privileges Fund on poverty in Yogyakarta using secondary data from the Central Bureau of Statistics for the period 2014-2023. The variables studied include poverty rate, Human Development Index (HDI), unemployment rate, and Gross Regional Domestic Product (GRDP) growth. The analysis was conducted using panel data regression method, using Fixed Effects Model and Non-Linear Logarithmic Panel Data Regression Model to capture data fluctuation more accurately. In addition, the Adaptive Regression Model was used to understand the dynamic relationship between variables. The results show that the Privilege Fund has not affected poverty in the year of allocation because the monitoring and evaluation process is carried out before the following year's allocation. Thus, the achievement of the Privileges Fund in the previous year (t-1) only has an impact on poverty reduction in the following year (t). HDI shows a significant negative effect on poverty in both models, while the unemployment rate has no effect. Meanwhile, GRDP growth has a significant negative effect on poverty in the Adaptive Panel Model but not in the Static Panel Model. These findings emphasize the importance of evaluation mechanisms in the effectiveness of the Privileges Fund as well as the role of human development and economic growth in reducing poverty in DIY.